2020
DOI: 10.1186/s13148-020-00852-2
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood DNA methylation reflects cord blood C-reactive protein levels but not maternal levels: a longitudinal study and meta-analysis

Abstract: Background: Prenatal inflammation has been proposed as an important mediating factor in several adverse pregnancy outcomes. C-reactive protein (CRP) is an inflammatory cytokine easily measured in blood. It has clinical value due to its reliability as a biomarker for systemic inflammation and can indicate cellular injury and disease severity. Elevated levels of CRP in adulthood are associated with alterations in DNA methylation. However, no studies have prospectively investigated the relationship between matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The DNAm of one CpG (3,500 base pairs upstream of the POU4F1 promoter) in cord blood was significantly associated with prenatal exposure to acetylsalicylic acid [30]. However, Yeung et al concluded that the association of prenatal acetylsalicylic acid exposure with DNAm in cord blood is negligible, as only one CpG with a minor effect size (1% increase in CpG DNAm) was discovered in their association study [30].…”
Section: Results Of Prenatal Medication Exposure and Neonatal Dna Methylationmentioning
confidence: 97%
See 3 more Smart Citations
“…The DNAm of one CpG (3,500 base pairs upstream of the POU4F1 promoter) in cord blood was significantly associated with prenatal exposure to acetylsalicylic acid [30]. However, Yeung et al concluded that the association of prenatal acetylsalicylic acid exposure with DNAm in cord blood is negligible, as only one CpG with a minor effect size (1% increase in CpG DNAm) was discovered in their association study [30].…”
Section: Results Of Prenatal Medication Exposure and Neonatal Dna Methylationmentioning
confidence: 97%
“…Although the studies report vastly different numbers of significant CpGs, both Gervin et al [35] and Addo et al [48] concluded that prenatal paracetamol exposure may be associated with DNAm in cord blood from susceptible individuals or placentae, respectively. Yeung et al [30] investigated the association between prenatal acetylsalicylic acid exposure and DNAm in cord blood. In the randomized controlled trial, women were randomly assigned to receive 81 mg of acetylsalicylic acid or placebo every day until conception (within six menstrual cycles) and during pregnancy [49].…”
Section: Results Of Prenatal Medication Exposure and Neonatal Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…n a l P r e -p r o o f serum and cord blood samples (48-51,54,55). In studies of paired mothers and neonates, cord blood levels of CRP were associated with DNA methylation changes in genes relevant to inflammation and angiogenesis in the neonate while maternal levels measured at multiple points over the course of pregnancy were not associated with DNA methylation in the neonate, implying that fetal levels of CRP were of particular relevance to epigenetic programming in comparison to maternal levels(55). We consider APP in NDBS as specific indicators of the neonatal innate immune status.CRP is a pattern recognition molecule, opsonin, and activator of the complement pathway(42).…”
mentioning
confidence: 99%